The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/875380
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Localized Osteitis in Mandibular Third-Molar Sites Using Platelet-Rich Fibrin

Abstract: Purpose. To review our experience utilizing platelet rich fibrin (PRF), which is reported to aid in wound healing of extraction sites, for the prevention of localized osteitis following lower third-molar removal. Materials and Methods. PRF was placed in the mandibular third-molar extraction sites, 200 sites total, on 100 consecutive patients treated in our practice, by the authors. The patients were managed with standard surgical techniques, intraoperative IV antibiotic/steroid coverage, and routine postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 16 publications
1
53
1
6
Order By: Relevance
“…Another important aspect of leukocyte biology that has not been discussed in this study, but again shows much clinical relevance, is the fact leukocytes are the responsible cell type acting to prevent infiltrating pathogens 32 , 33 . In light of this fact, it becomes of interest to note that PRF placed into extraction sockets has been shown to greatly decrease the rate of complications and infections 8 . Hoaglin and Lines 8 reported that filling third molar extraction sockets with PRF led to a 10‐fold decrease in osteomyelitis infections compared with natural healing.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Another important aspect of leukocyte biology that has not been discussed in this study, but again shows much clinical relevance, is the fact leukocytes are the responsible cell type acting to prevent infiltrating pathogens 32 , 33 . In light of this fact, it becomes of interest to note that PRF placed into extraction sockets has been shown to greatly decrease the rate of complications and infections 8 . Hoaglin and Lines 8 reported that filling third molar extraction sockets with PRF led to a 10‐fold decrease in osteomyelitis infections compared with natural healing.…”
Section: Discussionmentioning
confidence: 86%
“…In light of this fact, it becomes of interest to note that PRF placed into extraction sockets has been shown to greatly decrease the rate of complications and infections 8 . Hoaglin and Lines 8 reported that filling third molar extraction sockets with PRF led to a 10‐fold decrease in osteomyelitis infections compared with natural healing. This study, performed on 200 patients, used bilateral extractions (one side filled with PRF, the other left to naturally heal) and provided good scientific evidence for the reduced rate of infection after healing with PRF 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the available RCTs and controlled studies comparing L‐PRF to unassisted socket healing reported a benefit when L‐PRF was applied in terms of early (up to 8 weeks) (Alzahrani, Murriky & Shafik, ; Hauser, Gaydarov, Badoud, Vazquez & Bernard, ) and late (up to 16 weeks) (Temmerman, Vandessel, Castro, Jacobs & Teughels, ; Varghese, Manuel & Kumar, ) radiographic bone fill and horizontal/vertical alveolar preservation (Appendix S3), faster soft tissue healing, reduced pain and reduced post‐extraction sequelae (Marenzi, Riccitiello, Tia, Lauro & Sammartino, ; Ozgul, Senses, Er, Tekin & Tuz, ; Singh, Kohli & Gupta, ; Suttapreyasri & Leepong, ; Temmerman et al., ; Varghese et al., ; Zhang, Ruan, Shen, Tan & Huang, ). Moreover, the use of L‐PRF in third molars’ extractions has been associated with an improvement in second molars’ periodontal parameters (Kumar, Prasad, Ramanujam, Dexith & Chauhan, ) and a nearly tenfold decrease in the incidence of osteomyelitis compared to natural healing (Hoaglin & Lines, ). However, other RCTs and controlled studies did not confirm significant advantages when comparing L‐PRF to unassisted socket healing in terms of alveolar bone resorption and bone density (Girish Rao, Bhat, Nagesh, Rao & Mirle, ; Srinivas, Das, Rana, Qureshi & Vaidya, ; Zhang et al., ), periodontal parameters (Baslarli, Tumer, Ugur & Vatankulu, ), bone scintigraphy outcomes (Baslarli et al., ; Gurbuzer, Pikdoken, Urhan, Suer & Narin, ), post‐operative morbidities, prevention of dry socket and soft tissue closure (Asmael, Jamil & Hasan, ; Asutay, Yolcu, Gecor, Acar & Ozturk, ; Yerke, Jamjoom, Zahid & Cohen, ).…”
Section: Resultsmentioning
confidence: 99%
“…[7] Dry socket causes serious physical suffering for the patient, requires extra time and resources for its treatment, making it a socially significant illness. [8] The etiology of dry socket is not fully clarified, but the fibrinolysis and collapse of the blood coagulum as a result of bacterial invasion is the most common cause. [9] The causes of dry socket may be different: traumatic extraction, age, sex, smoking, contraceptive use, high concentration anesthetic, intraligamentary anesthesia, localization of the tooth, etc.…”
Section: Introductionmentioning
confidence: 99%